2018
DOI: 10.1016/j.cub.2018.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Color Sensing in Weakly Electric Fish Suggests Color Perception as a Sensory Concept beyond Vision

Abstract: Highlights d The weakly electric fish G. petersii perceives electric colors for prey recognition d Animals, plants, or prey provide specific electric colors during electrolocation d Electric color shares perceptual traits with visual color d Electric-color sensing in electric fish implies color perception beyond vision

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Although two parameters are not enough to determine the impedance of an object, it has been shown that one can define families of impedance values that, independently of their position, modify reafferent signals in such a way that phase and strength are related by a linear function, defining an electric qualia likened to 'electric color' (Budelli and Caputi, 2000). Recent experimental evidence supports this hypothesis (Gottwald et al, 2018).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Although two parameters are not enough to determine the impedance of an object, it has been shown that one can define families of impedance values that, independently of their position, modify reafferent signals in such a way that phase and strength are related by a linear function, defining an electric qualia likened to 'electric color' (Budelli and Caputi, 2000). Recent experimental evidence supports this hypothesis (Gottwald et al, 2018).…”
Section: Introductionmentioning
confidence: 79%
“…In pulse Mormyriformes, electroreceptors have a flat frequency sensitivity within a range of two orders of magnitude (Bell, 1990a, b). Thus, stimulus strength and phase spectrum may be considered the only two dimensions of a manifold where the 'electric color' of species, sex (Hopkins and Bass, 1981;Hopkins, 1986) and object impedance (von der Emde, 1990;von der Emde and Bleckmann, 1992;Gottwald et al, 2018) are represented. The present results show dual encoding of amplitude and phase spectral cues by each receptor type in G. omarorum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding EOD divergence, the major role of electrolocation in prey recognition is well established, as the natural habitat of Campylomormyrus has extremely low-light conditions due to the high-level of suspended particulate matter and turbidity in the system (Stiassny and Alter 2015), in addition to our species being nocturnal. Recent studies showed that nocturnal weakly electric fish perceive electric colors for fast and reliable prey recognition (Gottwald et al 2018). It has been shown that snout morphology and EOD characteristics are correlated, such that long putatively derived EODs are exhibited by long snouted species (Tiedemann et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work on mormyrid electrolocation has revealed that animals, plants, and invertebrates all create unique amplitude and waveform modulations referred to “electric colors” that allow these animals to reliably identify and differentiate these items (Gottwald et al. 2018), indicating that different EOD waveforms could therefore differ in their range of “electric color” detections.…”
Section: Discussionmentioning
confidence: 99%